(untitled) (ICEJ : Islamic Childhood Education Journal, 2022)
Independence in early childhood is an important aspect to be developed so that children are not dependent on others, in developing early childhood independence it can be done with outing class activities. 5-6 years through outing class activities at TK IT Qur’ani Adh Dhuhaa Pangkalpinang. Second, the results of the application of developing the independence of children aged 5-6 years through outing class activities at the IT Qur’ani Adh Dhuhaa Kindergarten in Pangkalpinang. The purpose of this study was to determine the outing class activities in developing the independence of children aged 5-6 years at TK IT Qur’ani Adh-Dhuhaa Pangkalpinang and also to know the results of implementing the development of independence for children aged 5-6 years through outing class activities at TK IT Qur’ani Adh. Duhaa Pangkalpinang. The results of this study indicate that there are several stages, namely planning, implementation stage, evaluation stage. With outing class activities, it can increase the independence of children aged 5-6 years and can also increase children’s knowledge according to the theme of learning, from outing class activities in developing children’s independence in this study shows that children’s independence can develop from initially not developing to developing as expected.